Insertion of a totally implantable vascular access device in a patient with dextrocardia and colon cancer: a case report - Mingyan Dong; Lihui Huang; Qiaohong Zhang; Yicui Piao; Zijie Liu; Shuchen Zhu; Haiguan Luo (Journal of International Medical Research, 2023)
Colon cancer in patients with situs inversus totalis is rarely associated with dextrocardia, and chemotherapy is commonly used for treatment. Central venous access devices are used to administer intravenous fluids and chemotherapy in patients with colon cancer. Compared with peripherally inserted central catheters and Hickman-type tunneled catheters, totally implantable vascular access devices (TIVADs) are safer and more effective. However, positioning the catheter tip may be challenging in patients with dextrocardia and situs inversus. We herein describe a novel case involving a patient with dextrocardia and colon cancer who was treated by TIVAD insertion with intracavitary electrocardiography-aided tip localization.